Changes in the Activity of the CLE41/PXY/WOX Signaling Pathway in the Birch Cambial Zone under Different Xylogenesis Patterns - Natalia A. Galibina; Yulia L. Moshchenskaya; Tatiana V. Tarelkina; Olga V. Chirva; Kseniya M. Nikerova; Aleksandra A. Serkova; Ludmila I. Semenova; Diana S. Ivanova (Plants, 2022)
The balance between cell proliferation and differentiation into other cell types is crucial for meristem indeterminacy, and both growth aspects are under genetic control. The peptide-receptor signaling module regulates the activity of the cambial stem cells and the differentiation of their derivatives, along with cytokinins and auxin. We identified the genes encoding the signaling module CLE41-PXY and the regulator of vascular cambium division WOX4 and studied their expression during the period of cambial growth in the radial row: the conducting phloem/cambial zone and the differentiating xylem in two forms of Betula pendula, silver birch and Karelian birch. We have shown that the expression maximum of the BpCLE41/44a gene precedes the expression maximum of the BpPXY gene. Non-figured Karelian birch plants with straight-grained wood are characterized by a more intensive growth and the high expression of CLE41/44-PXY-WOX4. Figured Karelian birch plants, where the disturbed ratio and spatial orientation of structural elements characterizes the wood, have high levels of BpWOX4 expression and a decrease in xylem growth as well as the formation of xylem with a lower vessel density. The mutual influences of CLE41-PXY signaling and auxin signaling on WOX4 gene activity and the proliferation of cambium stem cells are discussed.